UJI AKTIVITAS EKSTRAK Padina australis SEBAGAI ANTIBAKTERI Propionibacterium acnes PENYEBAB JERAWAT - Vira Mourena Putri Widjaya; Oom Komala; . Ismanto (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2021)
The apperance of acne is a problem for many suffers because can lower confidience and shame. Many people have attempted to treat or eliminate acne, that is by antibiotic. However of antibiotic clearly has side effects, and the ultilization of natural material is the solution. One of them is Padina australis which contains flavonoid, tanin dan saponin potentially as an antibacterial. The purpose of this research is to derermne the concentration of Padina australis extract with methanol 98% which has optimal activity in improving the growth of Propionibacterium acnes based on inhibition zone test and minimum inhibitory concetration (MIC). Qualitative phytochemical test were carried out on alkoloids, flavonoids, saponins, tannin and steroids. Testing these bacteria using disc dffusion methods. MIC of Padina australis extrct used dilution method with concentrtaion of 3.75%, 7.5%, 15% and 30%. Inhibition zone test used disc diffusion method with concentrtaion of 60%, 80% and 100%. The result of phytochemical screening testing Padina australis extrct test showed that there are secondary metabolite compounds alkoloids, flavonoids, saponins, tannin and steroids. MIC test of Padina australis extrct against Propionibacterium acnes occured at a concentration of 30% and the inhibition zone test was found at concentration of 100% which was the most optimal in inhibiting with an average of the inhibition zone width 6.20 mm.